Analysis of Factors affecting the Quality of Higher Education in India in comparison to the Global Scenario (International Journal of Innovative Research in Engineering & Management, 2021)
It has long been recognized that education was among the  most important determinants in a country's economic growth.  A developed country is always a well-educated country. As a  result, the learning process should be altered by current needs  and indeed the globalized context. After the United States and  China, India has the world's third-largest higher education  sector. Since freedom, India has struggled to make progress in  the area of education as a developing country. Following  independence, India's higher education sector has seen a huge  influx of universities and colleges. The private sector's  engagement in academia has been a game-changer for such  rapid expansion. This same Right to Education Legislation has  ushered in a sea shift in India's educational system. As India's  Higher Education System has faced several concerns and  challenges, it also has numerous chances to overcome these  obstacles and improve the system. The function of schools  and colleges in the new century, as well as rising scientific  knowledge on how individuals learn, all need increased  openness and accountability. India needs highly qualified and  educated individuals who can propel our economy ahead.  According to study, just 25% of engineering graduates are  immediately employable, and most institutions' educational  quality is inadequate. Neither Indian university has ever been  ranked among the top 200 universities in the world. This study  analyses the current state of higher education, as well as  identifying new concerns and challenges in the sector. Finally,  this study proposes a viable response in Higher Ed to  developing concerns and challenges.
Keywords: Accountability; Constitution; Globalization; Higher Education; Transparency